Viabilidade técnica do uso do lodo de estação de tratamento de água na produção de alface - Silva, Jose Luis Tavares da (2022)
In water treatment plants (WTP) procedures are developed that result in water potability, generate a residual by-product called WTP sludge, with polluting potential. The association of WTP sludge to commercial substrates seedling production is presented as an ecologically correct and economically viable alternative. The objective of this research was to analyze the technical feasibility of using WTP sludge added to four commercial substrates in the production of seedlings of five lettuce cultivars and their performance in the field, in Arapiraca, semiarid region of Alagoas. The research was divided into two stages. The 1st, at greenhouse level, the experiment was installed in a completely randomized design, 4 x 4 x 5 factorial scheme, considering the four commercial substrates (Pindstrup®, Vida Verde®, Bioplant 434® and Bioplant 401®), four levels of substrate replacement by sludge (0, 20, 40 and 60%) and five lettuce cultivars (‘Veneranda’, ‘Camila’, ‘Elba’, ‘Vitória Verdinha’ and ‘Diva’), with four replications. It was observed that the percentage of emergence was influenced by the addition of sludge, mainly in the Pindstrup substrate and at a dose of 60%, with 0% emergence. The seedling quality index (SQI) was influenced by the sludge doses, with the addition of up to 20% being recommended. In the 2nd experiment, the seedlings produced in the 1st stage were evaluated at field level, adopting a randomized block design, 3 x 3 x 5 factorial scheme, with three commercial substrates (Vida Verde, Bioplant 434 and Bioplant 401), three levels of substrate replacement by sludge (0, 20 and 40%) and five lettuce cultivars (‘Veneranda’, ‘Camila’, ‘Elba’, ‘Vitória Verdinha’ and ‘Diva’). Biometric variables were analyzed at harvest time, 25 days after transplanting. A triple interaction was observed for plant height, leaf length and yield. In general, all cultivars showed similar productivity (P>0.05) in up to 20% of sludge inclusion, regardless of substrate. Cultivars that had reduced SQI, in the 1st experiment, resumed growth and had similar productivity (0 up to 40% sludge), such as cultivars ‘Camila’ (Vida Verde), ‘Veneranda’ and ‘Diva’ (Bioplant 434) and ‘Veneranda’, ‘Camila’, ‘Elba’ and ‘Vitória Verdinha’ (Bioplant 401). The inclusion of sludge to replace the commercial substrate presents technical feasibility with potential for cost reduction and environmental preservation